PENGARUH STATUS PEKERJAAN DAN NEGARA PENEMPATAN TERHADAP REMITANSI PEKERJA MIGRAN INDONESIA - Prihanto, Purwaka Hari (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2014)
The objectives of this study are to analyse the growth of Indonesia migrant workers, and to analyse of remitance growth, also to examine the effect of employment, destination state of the remitance of Indonesia migrant workers.Â This study was done in Indonesia, using the pooled data from year 2009 to 2011, on 14 state destination of Indonesia migrant workers, and to analyse the data used multiple regression with helped SPSS program version 17. The results of study show that in periode of observation, the Indonesia migrant workers decline average 0.2 percent, while the remitance of Indonesia migrant workers growth with 0.6 percent. The regression model found that the remitance of Indonesia migrant workers determined by workers migrant in Formal sector, workers migrant in Informal Sector, and Destination State of migrant workers. Key words : Indonesian migrant workers, Remittance.